Thyroid disorders and COVID-19: a comprehensive review of literature - Anbardar, Narges; Dixon, Shanai Lashayla; Munugoti, Samhitha; Gaddam, Maneesh; Kashfi, Kebria; Kasulis, Lillian; Messersmith, Andrew L.; Asadipooya, Kamyar (Frontiers in Endocrinology, 2025)
BackgroundThe literature is rapidly evolving with regards to the endocrine consequences of coronavirus disease 2019 (COVID-19), including diabetes, thyroid dysfunction, adrenal and pituitary disorders. There is evidence suggesting that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection can lead to thyroid dysfunction and long-term sequelae. We aimed to review the current evidence and propose a preventive approach based on the published data since the beginning of the COVID-19 pandemic.MethodsA comprehensive review of literature was conducted using electronic databases PubMed and Google Scholar. Two authors independently used the keywords “Thyroid, Hypothyroidism, Hyperthyroidism, Graves, Thyroid Eye Disease, or Thyroiditis” and “Coronavirus, SARS-CoV-2 or COVID-19” to search these databases. We screened titles and abstracts for initial selection and then reviewed the full text of relevant studies to report the outcomes of published data.ResultsWe selected 28 manuscripts. SARS-CoV-2 infection appears similar to other viruses. It affects thyroid function resulting in non-thyroidal illness syndrome, which usually resolves spontaneously. COVID-19 also causes subacute thyroiditis. It may also trigger autoimmunity against the thyroid that leads to autoimmune thyroiditis. Autoimmune thyroiditis or subacute thyroiditis may progress to clinical or subclinical hypothyroidism and clinical or subclinical hyperthyroidism. Patients with pre-existing thyroid dysfunction probably have similar risks of SARS-CoV-2 related adverse outcomes.ConclusionsEvaluation of thyroid function is important in COVID-19 patients. Improving the efficacy of treatment against acute SARS-CoV-2 infection can reduce the risks of short-term and long-term complications.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero, identifier CRD42023447994.